2007
DOI: 10.1100/tsw.2007.14
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy: The Historical, Current, and Future Role in the Treatment of Pain

Abstract: Manual therapy has been an approach in the management of patients with various disorders dating back to ancient times and continues to play a significant role in current health care. The future role of manual therapy in health care is an important area of research. This paper reviews the history of manual therapy, examines the current literature related to the use of manual techniques (including manipulation, massage, and nerve manipulation), and discusses future research topics. The literature related to manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 83 publications
0
33
0
3
Order By: Relevance
“…Massage of tense, painful muscles has long been recognized as a method of relaxing them and reducing discomfort 17 . The term Laryngeal Manual Therapy (LMT) has been employed throughout this study as it is an 'umbrella' term which can be used to refer to any therapeutic handling of the laryngeal and perilaryngeal structures by a clinician.…”
Section: Insert Table 1 -Lmt and Mct -About Herementioning
confidence: 99%
“…Massage of tense, painful muscles has long been recognized as a method of relaxing them and reducing discomfort 17 . The term Laryngeal Manual Therapy (LMT) has been employed throughout this study as it is an 'umbrella' term which can be used to refer to any therapeutic handling of the laryngeal and perilaryngeal structures by a clinician.…”
Section: Insert Table 1 -Lmt and Mct -About Herementioning
confidence: 99%
“…32 Interestingly, although degenerative disc disease has long been thought to be an irreversible disease process, recent findings in vitro and in animal models have suggested that controlled loading and unloading of IVDs may result in some degree of regeneration. 17,24,25,30,33,38,43,48 Although the reason for this finding is unknown, improving diffusion of water in the IVDs by controlled loading and unloading of IVDs through the use of interventions such as lumbar traction, 7,11,12,23,46 joint manipulation, 9,12,26,45 repeated lumbar motions, 28,32 and graded abdominal muscle contraction 31 may be an important process that can favorably affect the internal chemical environment and mechanical properties of the degenerative IVD. However, it is currently unknown if this actually occurs.…”
Section: Test-retest Variability Of Adcmentioning
confidence: 99%
“…19 The body of evidence addressing the efficacy and effectiveness of interventions used by physical therapists to treat these patients continues to grow. 7,9,11,13,16,26,28,37,39,[45][46][47] Diffusion-Weighted Magnetic Resonance Imaging of Normal and Degenerative Lumbar Intervertebral Discs: A New Method to Potentially Quantify the Physiologic Effect of Physical Therapy Intervention structural changes within the annulus fibrosis, nucleus pulposis, and vertebral end plate can result in altered diffusion of water. 3,4,10,18,21,22,35,40 This process is thought to reduce the internal stability of the IVD and impair its load-bearing capacity, thereby resulting in symptoms during activity.…”
mentioning
confidence: 99%
“…(18)(19) Despite the benefits provided to patients who are treated with these techniques, these require the therapist great efforts in their musculoskeletal system, making it therefore more prone to DMEs. (20) Some studies show that physical therapists are highly prevalent in osteo-muscular disorders (21,22,23) , however, few have investigated the prevalence of DMEs in therapists who routinely use manual therapy to treat their patients.…”
Section: Disorders In Manual Therapistismentioning
confidence: 99%